2009
DOI: 10.1074/jbc.m807598200
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Signaling through EphrinA2-EphA2 Enhances Osteoclastogenesis and Suppresses Osteoblastogenesis

Abstract: Bone is remodeled constantly throughout life by bone-resorbing osteoclasts and bone-forming osteoblasts. To maintain bone volume and quality, differentiation of osteoclasts and osteoblasts is tightly regulated through communication between and within these two cell lineages. Previously we reported that cellcell interaction mediated by ephrinB2 ligand on osteoclasts and EphB4 receptor on osteoblasts generates bidirectional anti-osteoclastogenic and pro-osteoblastogenic signals into respective cells and presumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(176 citation statements)
references
References 32 publications
4
166
0
Order By: Relevance
“…Moreover, the blockage of ephrinB2/EphB4 interaction reduces mineralization of osteoblasts in vitro (Allan et al, 2008). Irie et al (2009) have recently reported that ephrinA2-EphA2 interaction promotes the initiation phase of bone remodeling by enhancing osteoclast differentiation and suppressing osteoblast differentiation. Thus, a communicating interaction between osteoclasts and osteoblasts regulates differentiation in both cells through their exchange of ephrin/ Eph signals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the blockage of ephrinB2/EphB4 interaction reduces mineralization of osteoblasts in vitro (Allan et al, 2008). Irie et al (2009) have recently reported that ephrinA2-EphA2 interaction promotes the initiation phase of bone remodeling by enhancing osteoclast differentiation and suppressing osteoblast differentiation. Thus, a communicating interaction between osteoclasts and osteoblasts regulates differentiation in both cells through their exchange of ephrin/ Eph signals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a reverse signal from EphB4 on the osteoblast inhibits osteoclast formation (Zhao et al, 2006). Interestingly, the interaction of ephrinA2-EphA2 inhibits osteoblast differentiation at the initiation phase of bone remodeling, whereas ephrinA2-EphA2 stimulate osteoclast formation (Irie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for this result lies in a report by Irie et al (2009) that EphA2 forward signaling in osteoblasts inhibits differentiation of cultured neonatal osteoblasts. In this scenario, unclustered EphA4/Fc might in fact counter both osteogenic EphB signals and inhibitory EphA2 signals, thus canceling each other out.…”
Section: Developmental Dynamicsmentioning
confidence: 99%
“…Ephs and ephrins are cell-surface molecules that signal bidirectionally and play major roles in tumor progression, angiogenesis, cell migration, and morphogenesis (16). Irie et al reported that bidirectional signaling through ephrinA2/EphA2 enhances osteoclastogenesis and suppresses OB differentiation (17). In contrast, ephrinB and EphB Paget's disease (PD) is characterized by focal and dramatic bone resorption and formation.…”
Section: Introductionmentioning
confidence: 99%